2019
DOI: 10.20452/pamw.14877
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of electrocardiographic signs of right ventricular overload after balloon pulmonary angioplasty in chronic thromboembolic pulmonary hypertension

Abstract: INTRODUCTION Balloon pulmonary angioplasty (BPA) is a treatment option for a patient with chronic thromboembolic pulmonary hypertension. OBJECTIVES We aimed to investigate the evolution of electrocardiographic (ECG) markers of right ventricular hypertrophy (RVH) after BPA. PATIENTS AND METHODS Standard 12-lead ECG was performed in 41 patients with chronic thromboembolic pulmonary hypertension before the first BPA and after completion of treatment. RESULTS In the whole study group, the percentage change in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Few previous studies have assessed the relationship between surface ECG and CTEPH for diagnostic and prognostic purposes [13,14,[20][21][22]. To the best of our knowledge, this is the first study that aims to characterize RVH ECG signs in newly diagnosed CTEPH patients and to relate these parameters to the localization of thromboembolic material along with hemodynamic data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few previous studies have assessed the relationship between surface ECG and CTEPH for diagnostic and prognostic purposes [13,14,[20][21][22]. To the best of our knowledge, this is the first study that aims to characterize RVH ECG signs in newly diagnosed CTEPH patients and to relate these parameters to the localization of thromboembolic material along with hemodynamic data.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an unfulfilled need to develop simple noninvasive tools to help clinicians identify patients with a high probability of CTEPH. Some previous studies revealed that in patients with pulmonary hypertension, the right heart overload is associated with the occurrence of the specific electrocardiographic changes [13,14]. There is a paucity of data regarding the role of noninvasive electrocardiography (ECG) in CTEPH diagnosis, management, and prognosticating.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies showed that unloading of the right ventricle in pulmonary hypertension can also improve several ECG parameters. In a study by Pilka et al, invasive treatment of CTEPH with balloon pulmonary angioplasty (BPA) was associated with a decrease in PVR and in mPAP, which was reflected by ECG improvement including a decrease in the frequency of negative T waves in leads V1–V3 from 55% before BPA to 22% after finishing BPA treatment [ 11 , 12 ]. Similar observations were found in a study by Nishiyama et al where negative T waves in V1–V3 were observed in 56% of patients before BPA and only in 8.3% after completing BPA treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who complete the BPA therapy require periodic, non-invasive control, as well as RHC. In previous studies, it has been documented that BPA therapy and an improvement in haemodynamic parameters are associated with significant changes in the resting ECG [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the group of patients with an inferior response, there were no significant changes in the above parameters. In the whole analysed population, the percentage change in the PVR was significantly correlated with the percentage change in the values of the following ECG parameters: axis of the QRS (rho = 0.530) and T wave (rho = 0.372), P wave amplitude in leads II (rho = 0.340) and III (rho = 0.430), S wave amplitude in lead V 5 (rho = 0.634), R/S amplitude ratio in lead V 5 (rho = –0.636), S wave amplitude in lead V 6 (rho = 0.508), and S wave amplitude in lead I (rho = 0.496) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%